Comparison of Different Autogenous Graft Materials for Reconstruction of Large Segment Vas Deferens Defect: Experimental Study in Rat - Nasir, Serdar; Soyupek, Sedat; Altuntas, Selman; Konas, Ersay; Roach, Emir Charles; Ozorak, Alper; Bircan, Sema (Urology Journal, 2014)
Abstract Purpose: Vasectomy is one of the most common urological operations performed, and provides permanent contraception. Many vasectomized men ultimately seek vasectomy reversalbecause of unforeseen changes in lifestyle. Vasovasostomy has varying rates of success. Inthis study, we utilize vas deferens (VD), artery, and vein grafts to reconstruct 30% and 50%defects of the total vas deferens length. Materials and Methods: Forty two male Wistar rats were divided into three groups as VDgraft, carotid artery and external jugular vein transplantations. Each group was equally dividedinto 2 different subgroups according to the length of transplant material as 1.0 cm (n = 7) and1.5 cm (n = 7). To evaluate whether these materials may be used for long segment vas deferensreconstruction, the patency rate, partial or total graft occlusion, and histologic examination ofall specimens were examined. Results: No patency was found in any of the grafts and many of them suffered destructivechanges in anatomic structure. Sperm granulomas were determined around the testicular sideanastomosis due to accumulated semen fluid which was in our belief, a result of aperistalticzone caused by the grafts. Conclusion: When the poor results obtained in our study are put into perspective, vasoepididymostomyis the only treatment method to date for reconstruction of large segment vasdeferens defects.